2022
DOI: 10.1001/jamaoto.2022.0890
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patients With Head and Neck Cancer in Randomized Clinical Trials and Clinical Practice

Abstract: IMPORTANCE When patient populations in randomized clinical trials deviate too much from the general population, it undermines the relevance for daily practice.OBJECTIVE To investigate if patients with head and neck cancer in randomized clinical trials are representative of the clinically treated population.EVIDENCE REVIEW A systematic literature search was performed for randomized clinical trials on head and neck cancer evaluating an intervention to improve outcome with total sample size of 100 patients or gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…However, patients selected for participation in clinical trials have been reported to display better performance status and younger age than patients treated in clinical practice. 28 Nevertheless, our cohort showed 2-year OS of 96.6%, 88.9%, and 94.2% for patients with low, intermediate, and highrisk diseases, respectively. Furthermore, we show favorable 5-year DSS of 100.0%, 90.0%, and 88.7% in patients with low, intermediate, and high-risk diseases.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, patients selected for participation in clinical trials have been reported to display better performance status and younger age than patients treated in clinical practice. 28 Nevertheless, our cohort showed 2-year OS of 96.6%, 88.9%, and 94.2% for patients with low, intermediate, and highrisk diseases, respectively. Furthermore, we show favorable 5-year DSS of 100.0%, 90.0%, and 88.7% in patients with low, intermediate, and high-risk diseases.…”
Section: Discussioncontrasting
confidence: 53%
“…Indeed, 2‐year OS in low‐risk patients was 96–100% irrespective of treatment arm or risk. However, patients selected for participation in clinical trials have been reported to display better performance status and younger age than patients treated in clinical practice 28 . Nevertheless, our cohort showed 2‐year OS of 96.6%, 88.9%, and 94.2% for patients with low, intermediate, and high‐risk diseases, respectively.…”
Section: Discussionmentioning
confidence: 66%
“…The data of Ang et al were based on a retrospective analysis of patients with stage III–IV 7 th ed. OPC included in the RTOG0129 randomized trial between 2002 and 2005 treated with high-dose cisplatin, with a subsequent selection that may have excluded older or unfit patients [ 29 , 30 ]. However, time-dependent age evaluation may be an issue for comparison of published cohorts when HPV-positive and HPV-negative patients are not studied over exactly the same period of time.…”
Section: Discussionmentioning
confidence: 99%